Semantic Connection : Rancangan Platform Komunikasi pada Smart Object - Iwan Kurnianto Wibowo (JURNAL NASIONAL TEKNIK ELEKTRO, 2016)
To provide a better gaming experience, it needs to design a game framework using smart object media as interaction media with various scenarios. In previous researchs have built a game media such as a smart object. Smart objects are physically integrated with the sensor, processor, and network. Smart object able to sense, interpret what is happening with him and their surroundings, reacting, interacting with other objects and exchanging information with the user. Media interaction is closely related to the communication platforms used. This paper presents a communication platform on smart object. The communication platform provides mechanisms of smart object to serve the interaction with other smart object and communicates with server. The smart object functions as universal input and output device based embedded systems that have a communication protocol.  So that many game scenarios can be implemented. Data communication between the smart object and the server is done wirelessly and full duplex, between data receiving and trasmitting lines are separated and worked simultaneously. Point to multipoint data transmission adopts star topology. The server is connected directly to each smart object. Data transmission between a smart object to the server generates an error rate of up to 0.15%. When there are three smart object that communicates with the server, the error rate increased to 2.77%.Keywords : Gaming Experience, Smart Object, Communication PlatformAbstrak—Untuk memberikan pengalaman bermain lebih mendalam, perlu disusun kerangka permainan yang memanfaatkan media smart object sebagai media interaksi dengan skenario yang bervariasi. Pada penelitian sebelumnya telah dibangun sebuah media permainan berupa smart object. Smart object secara fisik terintegrasi dengan sensor, prosesor, dan jaringan. Smart object mampu merasakan, menafsirkan apa yang terjadi dengan dirinya dan lingkungan sekitar, bereaksi, berinteraksi dengan objek lainnya dan bertukar informasi dengan pengguna. Media interaksi erat kaitannya dengan platform komunikasi yang digunakan. Makalah ini menyajikan platform komunikasi pada smart object yang telah dibangun. Platform komunikasi meliputi mekanisme smart object dalam melayani interaksi dengan smart object lain dan komunikasi dengan server. Smart object berfungsi sebagai perangkat masukan dan keluaran universal berbasis sistem embedded yang ditanamkan sebuah protokol dalam berkomunikasi. Sehingga banyak skenario permainan yang dapat diimplementasikan. Komunikasi data antara smart object dan server dilakukan secara nirkabel dan full duplex, antara jalur penerimaan dan pengiriman data terpisah dan bekerja secara bersamaan. Pengiriman data point to multipoint mengadopsi topologi bintang. Server terhubung langsung ke masing-masing smart object. Pengiriman data antara sebuah smart object ke server menghasilkan tingkat kesalahan hingga 0.15%.  Ketika ada tiga smart object yang berkomunikasi dengan server maka tingkat kesalahan meningkat hingga 2.77%.Kata Kunci : Pengalaman permainan, Smart object, Platform komunikasi